EVALUATION OF ANTIOXIDANT ACTIVITY OF SEERAGA CHOORANAM IN- VITRO ASSAY (A SIDDHA POLYHERBAL PREPARATION) - Keerthana, *R; Visweswaran, S; Sivakkumar, S; Maariappan, A; Banumathi, V (International Journal of Ayurveda and Pharma Research, 2018)
Siddha Medicine (Tamil Citta- or Tami?-maruttuvam) is a system of traditional medicine originating in Tamil Nadu in South India. The drugs used by the Siddhars could be classified into three groups: Thaavaram, Thaathu and Jangamam seeraga chooranam is a drug under the category of Thaavaram. It is a poly herbal formulation which is mentioned in the text Pullipanivaithyam 500 which has been therapeutically used for Pithanoigal, Kirukirupu, Vaanthi, Mayakkam, Ajeeranam, Kaangai, Veppam.Siddha system emphasis mainly on healthy long life by preventing ageing and degenerative disease with medicines having antioxidant activity. Even though this drug has been used based on traditional knowledge no scientific work has been done to evaluate the antioxidant properties of Seeraga choornam based on various in vitro assays. The study result confirmed that the drug Seeraga choornam has promising therapeutic antioxidant activity when compared with the standard drug. This research work can help for medical practitioners to use this polyherbal compound for the treatment of cancer.